2010
DOI: 10.1186/1475-9276-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors differentiating maternal and child health-seeking behavior in rural Bangladesh: A cross-sectional analysis

Abstract: BackgroundThere has been an increasing availability and accessibility of modern health services in rural Bangladesh over the past decades. However, previous studies on the socioeconomic differentials in the utilization of these services were based on a limited number of factors, focusing either on preventive or on curative modern health services. These studies failed to collect data from remote rural areas of the different regions to examine the socioeconomic differentials in health-seeking behavior.MethodsDat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
187
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(228 citation statements)
references
References 32 publications
38
187
0
3
Order By: Relevance
“…This is similar to findings in some similar studies conducted in Nigeria, some other African countries and in rural Bangladesh. 13,14,16,19,21,22 Issue of financial constraints, traditional beliefs, cultural inhibitions and ignorance about importance and need for ANC and delivery also emerged from the FGD -Examples are these statements from some of the participants. Some of these reasons such as expense of care, home comfort, no permission from husbands, and poor attitude of health workers were also reported from the study from Kano by Doctor et al 12 These findings are also consistent with some of the findings in a similar study by Titaleyet al in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to findings in some similar studies conducted in Nigeria, some other African countries and in rural Bangladesh. 13,14,16,19,21,22 Issue of financial constraints, traditional beliefs, cultural inhibitions and ignorance about importance and need for ANC and delivery also emerged from the FGD -Examples are these statements from some of the participants. Some of these reasons such as expense of care, home comfort, no permission from husbands, and poor attitude of health workers were also reported from the study from Kano by Doctor et al 12 These findings are also consistent with some of the findings in a similar study by Titaleyet al in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that prevent women from receiving or seeking health care during pregnancy and childbirth include inadequate services, poverty, distance, lack of information, and cultural practices (UNICEF 2012). In Bangladesh studies have found that education, household socioeconomic status, and urban-rural residence are consistently significant predictors of service utilization (Amin et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To predict the SES of the patient, a pool of potential indicators of both dimensions of the SES was collected from previous studies (Amin et al, 2010, Durkin et al, 1994, Shavers, 2007, Tiwari & Kumar, 2005. These indicators were pre-tested and validated in different socioeconomic contexts.…”
Section: Univariate Measures As Socioeconomic Indicatorsmentioning
confidence: 99%